Managerial Economics : Economic Tools for Today's Decision Makers. - Keat, Paul G; Young, Philip K Y; Erfle, Stephen E; Banerjee, Sreejata (Upper Saddle River : Pearson, 2019)
Aimed at advanced-level undergraduate and graduate courses in managerial economics, this text features running case studies exploring hypothetical decision-making processes. It creates a setting that highlights microeconomic theory and the tools of quantitative analysis.
Keywords: Managerial economics